2019
DOI: 10.1049/iet-epa.2018.5559
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of iron loss of the inner yoke in electromagnetic linear actuator

Abstract: The iron loss of inner yoke accounts for the majority of iron loss of an electromagnetic linear actuator (ELA). Therefore, the reduction of iron loss of inner yoke is of great importance to the reduction of iron loss of the whole ELA. This study investigates the formation mechanism and distribution law of ELA iron loss and proposes a reduction scheme by arranging groove structures in the inner yoke. The direction of groove arranged in inner yoke was determined based on the formation mechanism of inner yoke iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Cheng et al [34] designed an HSV with an Fe-based nano-crystalline soft magnetic alloy using metal injection molding technology, which improved the performance of soft magnetic materials, reduced the Eddy current loss of the HSV, and improved the dynamic response speed. Dai et al [35] and Zhao et al [25,26] found that grooving on the iron core can suppress the Eddy effect to a certain extent and enhance the dynamic response speed of the HSV.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al [34] designed an HSV with an Fe-based nano-crystalline soft magnetic alloy using metal injection molding technology, which improved the performance of soft magnetic materials, reduced the Eddy current loss of the HSV, and improved the dynamic response speed. Dai et al [35] and Zhao et al [25,26] found that grooving on the iron core can suppress the Eddy effect to a certain extent and enhance the dynamic response speed of the HSV.…”
Section: Introductionmentioning
confidence: 99%
“…A new method was analyzed in [10], which focused on enhancing the stacking factor and air-gap flux density by designing the stator pole end and back iron in separate formations. To reduce the mover core losses, a scheme of making groves was investigated in [11]. This formation scheme reduced the mover core losses significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Linear oscillating actuator (LOA) is an electromechanical system which provides mover's (piston's) reciprocating motion on the same axis without any intermediate mechanism such as gears, screws, or crank shaft [4]. Key advantages of LOA are higher oscillation frequency, lower power consumption and lower manufacturing cost [5]. Based on the configuration of moving part (mover), LOAs are classified as moving coil, moving iron and moving magnet type actuators [6].…”
Section: Introductionmentioning
confidence: 99%